Efektivitas Jus Buah Naga Merah (Hylocerus Polyrhizus) terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil - Desmariyenti Desmariyenti; Zurhayati Zurhayati; Nurul Hidayah (LPPM Hang Tuah Pekanbaru, 2023)
In 2013, 37.1% of pregnant women in Indonesia suffered from anemia, increasing to 48.9% in 2018. Red dragon fruit can be used as an alternative food ingredient to increase Hb and human red blood cell levels. The purpose of this study was to determine the effectiveness of red dragon fruit juice in the working area of ​​PMB Rosita Pekanbaru in 2022 on the increase in Hb levels in pregnant women at the end of pregnancy. This study uses a quasi-experimental design. The population of this study consisted of 50 late-pregnancy mothers with mild and moderate anemia. The sample is 15 people. Data processing was the Wilcoxon test. Based on the results of the Wilcoxon test, Pvalue (0,001) and degree of error = 0.05 (Pvalue <α), then Ha accepted, Ho was rejected, red dragon fruit juice was effective in increasing hemoglobin levels in pregnant women at PMB Rosita Pekanbaru. It is hoped that the research site can provide information about the effectiveness of red dragon fruit juice in increasing Hb levels of pregnant women in Trismerter III.